Understandings the reading habit and reading attitudes among students in research university library in Malaysia / Samsul Farid Samsuddin and Yanti Idaya Aspura. - Samsul Farid Samsuddin, Samsul Farid; Aspura, Yanti Idaya (Perpustakaan Tun Abdul Razak (PTAR), 2021)
Reading is one of the activities known to give a lot of benefits to readers. In the context of university students, reading can improve their academic performance. However, literature indicated that students read-only to pass their examination and not for pleasure and acquiring knowledge. The study reported in this paper investigated the reading habit and reading attitudes among students in the research university library in Malaysia. It is believed that positive reading attitudes towards education materials or non-education materials lead to positive reading experiences, which also lead to higher academic performance. A descriptive study used questionnaires as an instrument of a quantitative method. Convenience sampling was employed and 400 respondents from four research university status libraries were selected. Moderate levels of reading attitude were obtained from the result of the study, in which several variables produced a significant relationship in the reading attitude (education background and favorite activities during leisure time). The findings of this study have shown the behavior of academic library users in terms of reading habits, reading attitudes, and selection of reading materials. Several suggestions such as providing a variety of reading material (sense of humor and humanities, public figures and tv personalities) and reading encouragement activities have been suggested. This study provides useful inputs to the Ministry of Higher Education (MOHE) in constructing effective strategies to cultivate reading habits among reluctant readers in public universities.